Unlocking the potential of lauric acid: A promising solution for battery thermal management - Altuntop, Enis Selcuk; Erdemir, Dogan; Kaplan, Yuksel; Ozceyhan, Veysel (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2025)
This paper presents a comprehensive experimental investigation into the thermal management of lithium-ion batteries using lauric acid as a phase change material (PCM). The study explores the effectiveness of lauric acid under various design and operating conditions, including different battery pack voltages (12V, 24V, 48V), cell spacing (0.25D, 0.5D, and 1D - D: diameter of battery), discharge rates (1C, 2C, 3C, 4C, and 5C), and the incorporation of active air cooling that uses varying external air velocities (5, 7.5, and 10 m/s). The results demonstrate that the hybrid cooling system can maintain the desired temperature, which is below the melting point of lauric acid (43-45 degrees C). The hybrid cooling system has successfully reduced the temperature differences within the battery pack, consistently maintaining them below 5 degrees C. The energy efficiencies exceeded 80 % and approached 90 % in most cases. These observations indicate the capability of lauric acid to maintain battery temperatures within safe operating limits, reduce temperature differences within the pack, and achieve high energy efficiency. This research highlights the potential of lauric acid as a promising, cost-effective, and safe PCM solution for battery thermal management systems, particularly in long-term applications.
Keywords: Battery; Battery pack; Battery thermal management system; Lithium-ion battery; Lauric acid; Phase change material (PCM); PHASE-CHANGE MATERIALS; Thermodynamics; Engineering